Computer Program for Analysis and Design of Nanostructured Semiconductor Devices - Tanaka, Roberto Yuji; Passaro, Angelo; Abe, Nancy Mieko; Sperotto, Lucas Kriesel; Pedroso, Diogo de Moura [UNESP]; Vieira, Gustavo Soares; IEEE (Ieee, 2013)
This work presents the recent improvements in a computer program created to assist the design and analysis of quantum well, wire, and dot nanostructured semiconductor-based devices. The list of added features includes the calculation of heavy hole, light hole and split-off energy bands, dark current, photocurrent, and absorption spectrum. Additionally, the computer program allows self-consistent computation and can take into account the energy band non-parabolic effects in the effective mass approximation.
Keywords: quantum wells; quantum dots; finite element methods; nanotechnology; computer aided engineering; software development